Quantitative and Qualitative Analysis of Transient Fetal Compartments during Prenatal Human Brain Development - Vasung, Lana; Lepage, Claude; Radoš, Milan; Pletikos, Mihovil; Goldman, Jennifer S.; Richiardi, Jonas; Raguž, Marina; Fischi-Gómez, Elda; Karama, Sherif; Huppi, Petra S.; Evans, Alan C.; Kostovic, Ivica (Frontiers in Neuroanatomy, 2016)
The cerebral wall of the human fetal brain is composed of transient cellular compartments, which show characteristic spatiotemporal relationships with major neurogenic events (proliferation, migration, axonal growth, dendritic differentiation, synaptogenesis, cell death, and myelination). The aim of the present study was to obtain new quantitative data describing volume, surface area, and thickness of transient compartments in the human fetal cerebrum. Forty-four postmortem fetal hemispheres aged 13-40 postconceptional weeks (PCW) were included in this study. High-resolution TI MRI was acquired on 19 hemispheres and MRI images were processed using the MNI-ACE toolbox. Delineation of fetal compartments was performed semi-automatically by co-registration of MRI with histological sections and age-matched brains from Zagreb Neuroembryological Collection. Growth trajectories of transient fetal compartments were reconstructed and the composition of telencephalic wall was quantitatively assessed. Between 13 and 25 PCW, when the intensity of neuronal proliferation decreases drastically, the relative volume of proliferative (ventricular and subventricular) compartments showed pronounced decline. In contrast, synapse- and extracellular matrix-rich subplate compartment continued to grow during the first two trimesters, occupying up to 45% of telencephalon and reaching its maximum volume and thickness around 30 PCW. This developmental maximum coincides with a period of intensive growth of long cortico-cortical fibers, which enter and wait in subplate before approaching the cortical plate. Although we did not find significant age related changes in thickness of the cortical plate, the volume, gyrification index, and surface area of the cortical plate continued to exponentially grow during the last phases of prenatal development. This cortical expansion coincides developmentally with the transformation of embryonic cortical columns, dendritic differentiation, and ingrowth of axons. These results provide a normative, quantitative description of transient human fetal brain compartments observable with MRI, will improve understanding of structural-functional relationships, enable correlation between in vitro/in vivo imaging and fine structural histological studies, and will serve as normative for study of perinatal brain injuries.